SHEAR PERFORMANCE OF SPECIAL DRY JOINTS FOR PRECAST CONCRETE SEGMENTS (ASEAN Engineering Journal, 2021)
The special dry joints for precast prestressed concrete segments are invented in this study toovercome the limitation of conventional dry joints. Eight specimens of special dry joints were madeand subjected to direct shear test. Test parameters comprise concrete compressive strength (normaland high strength concrete) and steel fiber volume added in the special dry joint (0%, 0.5%, and1.0%). Test results revealed that the inclusion of steel fibers remarkably enhanced the shear capacityand ductility index. Failure mode of specimens was changed from shearing off to concrete crackingaround shear key corners, defined as ductile shearing-off failure. Furthermore, the existing equationsfor predicting shear capacity of keyed joints were validated by the experimental results. Amongavailable equations from literatures, the Turmo’s equation yields better prediction of the shearcapacity for the special dry joint made with normal strength concrete.